2011
DOI: 10.1007/s13539-011-0019-5
|View full text |Cite|
|
Sign up to set email alerts
|

Wasting in chronic kidney disease

Abstract: Wasting/cachexia is prevalent among patients with chronic kidney disease (CKD). It is to be distinguished from malnutrition, which is defined as the consequence of insufficient food intake or an improper diet. Malnutrition is characterized by hunger, which is an adaptive response, whereas anorexia is prevalent in patients with wasting/cachexia. Energy expenditure decreases as a protective mechanism in malnutrition whereas it remains inappropriately high in cachexia/wasting. In malnutrition, fat mass is prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
241
2
12

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(261 citation statements)
references
References 141 publications
(202 reference statements)
6
241
2
12
Order By: Relevance
“…Vitamin D deficiency is common in patients with chronic kidney disease (CKD),4 a population in whom muscle wasting and weakness are also highly prevalent 5, 6, 7. Observational studies have shown that circulating 25‐hydroxyvitamin D [25(OH)D] levels are reduced in parallel to the severity of muscle symptoms 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency is common in patients with chronic kidney disease (CKD),4 a population in whom muscle wasting and weakness are also highly prevalent 5, 6, 7. Observational studies have shown that circulating 25‐hydroxyvitamin D [25(OH)D] levels are reduced in parallel to the severity of muscle symptoms 8.…”
Section: Introductionmentioning
confidence: 99%
“…These observations collectively imply an integrated role of vitamin D for bone and muscle health. Such a role may have substantial clinical implications, especially for CKD patients, in which musculoskeletal alterations and their complications, including muscle pain and weakness, sarcopenia, fatigability, reduced exercise tolerance, fractures, and falls, adversely affect quality of life and survival 12, 13, 14, 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A serious complication of these chronic illnesses is cachexia. Cachexia is defined as weight loss greater than 5% of body weight in 12 months or less in the presence of chronic illness or as a body mass index (BMI) lower than 20 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Significant progress has been made defining cachexia and its associated clinical characteristics in patients with cancer. An agreed definition and classification of cancer cachexia 8 has contributed to enhanced standardization of screening, staging assessment and management.…”
Section: Diagnosismentioning
confidence: 99%